The use of ECT and MST in treating depression. - Allan, C; Ebmeier, K (2011)
Electroconvulsive therapy (ECT) has been used clinically since 1938. Its most common use is in the treatment of depression: first line treatment where rapid recovery is a priority, but more frequently as an effective treatment for patients who do not respond to pharmacological and psychological approaches. Whilst it is widely hailed as an effective treatment, concerns about its effect on cognition remain. The development of magnetic seizure therapy (MST) over the past decade has attempted to devise a therapy with comparable efficacy to ECT, but without the associated cognitive side effects. The rationale for this is that MST uses magnetic fields to induce seizures in the cortex, without electrical stimulation of brain structures involved with memory. MST has been used successfully in the treatment of depression, yet there is a dearth of literature in comparison with ECT. We present a systematic review of the literature on ECT (from 2009-2011) and MST (from 2001-2011).